Product quality. Price perception increasing Brand Image: The Mediating Role of Social Media Marketing - Ahmad Wijayanto; Parlagutan Silitonga (LPPM Universitas Asa Indonesia, 2023)
The purpose of this research is to improve the citra merek of Carl's jr Grand Indonesia with product quality and price perceptions through social media marketing. The population in this study were all customers of Carl's Jr. Grand Indonesia, and the sampling technique used accidental sampling with 190 respondents. The method for collecting data utilizes questionnaires distributed to respondents . The analysis used is path analysis with the SmartPLS 3.2.9. The research results show that product quality variables have no influence on brand image through social media marketing. Meanwhile, product quality has a positive influence on brand image, price perception has a positive influence on brand image, price perception has a positive influence on brand image through social media marketing, and social media marketing has a positive influence on social media marketing. So it can be concluded that apart from the hypothesis being rejected, all the hypotheses in this study have an important role in Increasing the brand image of Carl's Jr.